Conformational polymorphism or structural invariance in DNA photoinduced lesions: implications for repair rates. Issue 7 (28th February 2017) - Dehez, François; Gattuso, Hugo; Bignon, Emmanuelle; Morell, Christophe; Dumont, Elise; Monari, Antonio
Abstract: DNA photolesions constitute a particularly deleterious class of molecular defects responsible for the insurgence of a vast majority of skin malignant tumors. Dimerization of two adjacent thymines or cytosines mostly gives rise to cyclobutane pyrimidine dimers (CPD) and pyrimidine(6-4)pyrimidone 64-PP as the most common defects. We perform all-atom classical simulations, up to 2 μs, of CPD and 64-PP embedded in a 16-bp duplex, which reveal the constrasted behavior of the two lesions. In particular we evidence a very limited structural deformation induced by CPD while 64-PP is characterized by a complex structural polymorphism. Our simulations also allow to unify the contrasting experimental structural results obtained by nuclear magnetic resonance or Förster Resonant Energy Transfer method, showing that both low and high bent structures are indeed accessible. These contrasting behaviors can also explain repair resistance or the different replication obstruction, and hence the genotoxicity of these two photolesions.